Odpowiedzi

2009-12-16T19:39:53+01:00
A)
3x = 12
x - y = 1

x=4
4-y=1

x=4
-y=-3

x=4
y=3

b)
5y = 2
x + y = 2 2/5

y=2/5
x+2/5 =2 2/5

y=2/5
x= 12

c)
4y - x = 6
17y= 0

x=-6
y=0

d)
a = b
2a + b = 9

a=b=3

e)
u = 4v
5u - v = 10

u=4v
20v-v=10

u=4v
19v=10

u=4v
v= 10/19

u=40/19
v10/19

f)
3r = s
3r + s = 24

s=12
r=4

2009-12-16T19:42:12+01:00
A) 3x = 12 |:3
x - y = 1

x=4
4-y=1

x=4
-y=-3 |*(-1)

x=4
y=3
b) 5y = 2 |:5
x + y = 2 2/5

y=2/5
x+2/5=2 2/5

y=2/5
x=2
c) 4y - x = 6
17y= 0 |:17

4*0-x=6
y=0

x=-6
y=0
d)a = b
2a + b = 9

a=b
3a=9 |;3

a=b
a=3
e) u = 4v
5u - v = 10

u=4v
5*4v-v=10

u=4v
19v=10 |:19

u=4*10/19
v=10/19

u=2 2/19
v=10/19
f) 3r = s
3r + s = 24

3r=s
3r+3r=24 |:6

s=3r
r=4

s=12
r=4
2009-12-16T19:43:30+01:00
A) 3x=12
x-y=1 /*(-3)

3x=12
-3x+9y=-3
____________
9y=9/:9
y=1

x-1=1
x=1+1
x=2

x=2
y=1

b)5y=2
x+y=2⅖

5y=2
y+x=2⅖ /*(-5)

5y=2
-5y-4x=-12
__________
-4x=-10 /: (-4)
x=2½

-5y-10=-12
-5y=10-12
-5y=-2 /:(-5)
y=⅖

x=2½
y=⅖